Preeclamptic Women Have Disrupted Placental microRNA Expression at the Time of Preeclampsia Diagnosis: Meta-Analysis - Cirkovic, Andja; Stanisavljevic, Dejana; Milin-Lazovic, Jelena; Rajovic, Nina; Pavlovic, Vedrana; Milicevic, Ognjen; Savic, Marko; Kostic Peric, Jelena; Aleksic, Natasa; Milic, Nikola; Stanisavljevic, Tamara; Mikovic, Zeljko; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
INTRODUCTION: Preeclampsia (PE)is a pregnancy-associated, multi-organ, life-threatening disease that appears after the 20th week of gestation. The aim of this study was to perform a systematic review and meta-analysis to determine whether women with PE have disrupted miRNA expression compared to women who do not have PE. METHODS: We conducted a systematic review and meta-analysis of studies that reported miRNAs expression levels in placenta or peripheral blood of pregnant women with vs. without PE. Studies published before October 29, 2021 were identified through PubMed, EMBASE and Web of Science. Two reviewers used predefined forms and protocols to evaluate independently the eligibility of studies based on titles and abstracts and to perform full-text screening, data abstraction and quality assessment. Standardized mean difference (SMD) was used as a measure of effect size. RESULTS: 229 publications were included in the systematic review and 53 in the meta-analysis. The expression levels in placenta were significantly higher in women with PE compared to women without PE for miRNA-16 (SMD=1.51,95%CI=0.55-2.46), miRNA-20b (SMD=0.89, 95%CI=0.33-1.45), miRNA-23a (SMD=2.02, 95%CI=1.25-2.78),miRNA-29b(SMD=1.37, 95%CI=0.36-2.37), miRNA-155 (SMD=2.99, 95%CI=0.83-5.14) and miRNA-210(SMD=1.62, 95%CI=0.78-2.46), and significantly lower for miRNA-376c (SMD=-4.86, 95%CI=-9.51 to -0.20).An increased level of miRNK-155expression was found in peripheral blood of women with PE (SMD=2.06, 95%CI=0.35-3.76), while the expression level of miRNA-16 was significantly lower in peripheral blood of PE women (SMD=-0.47, 95%CI=-0.91 to -0.03).The functional roles of the presented miRNAs include control of trophoblast proliferation, migration, invasion, apoptosis, differentiation, cellular metabolism and angiogenesis. CONCLUSION: miRNAs play an important role in the pathophysiology of PE. The identification of differentially expressed miRNAs in maternal blood creates an opportunity to define an easily accessible biomarker of PE.